An Ancient Chinese Herbal Decoction Containing Angelicae Sinensis Radix, Astragali Radix, Jujuba Fructus, and Zingiberis Rhizoma Recens Stimulates the Browning Conversion of White Adipocyte in Cultured 3T3-L1 Cells. (16th June 2019) - Gong, Guowei; Han, Guangyi; He, Huan; Dong, Tina T. X.; Tsim, Karl W. K.; Zheng, Yuzhong
Abstract : Background . Abnormal storage of white adipocyte tissue (WAT) is the major factor causing obesity. The promising strategies for obesity treatment are building up the brown adipocyte tissue (BAT) and/or expedite fatty acid catabolism. Traditional Chinese Medicine (TCM) sheds light on preventing obesity. Ginger is one of the most effective herbs for antiobesity by accelerating browning WAT. To fortify the antiobesity effect of ginger, an ancient Chinese herbal decoction composed of four herbs, Angelicae Sinensis Radix (ASR), Astragali Radix (AR), Jujuba Fructus (JF), and Zingiberis Rhizoma Recens (ZRR; ginger), was tested here: this herbal formula was written in AD 1155, named as Danggui Buxue Tang (DBT1155 ). Therefore, the antiobesity function of this ancient herbal decoction was revealed in vitro by cultured 3T3-L1 cells. Materials and Method . The lipid accumulation was detected by Oil Red O staining. Furthermore, the underlying working mechanisms of antiobesity functions of DBT1155 were confirmed in 3T3-L1 cells by confocal microscopy, western blot, and RT-PCR. Results . DBT1155 was able to actuate brown fat-specific gene activations, which included (i) expression of PPAR γ, UCP1, and PCG1 α and (ii) fatty acid oxidation genes, i.e., CPT1A and HSL. The increase of browning WAT, triggered by DBT1155, was possibly mediated by a Ca 2+ -AMPK signaling pathway, because the application of Ca 2+ chelator, BAMPTA-AM, reversed the effect. Conclusion . These findings suggested that the herbal mixture DBT1155 could potentiate the antiobesity functions of ginger, which might have potential therapeutic implications.